REPRESENTATION OF SOCIAL CLASSS IN PARASITE MOVIE - Sihombing, Lambok Hermanto; Sinaga, Agustinus Alexander (Lire Journal (Journal of Linguistics and Literature), 2021)
Film works can be created from various perspectives and production methods by teams in the film industry. Parasite is a South Korean movie present as a production-based film and it raises a big theme of lifestyle differences between social classes. Parasite Movie portrays a new perspective with an astonishing story and plot-twist in the context of film with the issue of social inequality in the modern era. Various awards were obtained by Parasite films on a national and international scale for its beautiful story. The data is collected from the scenes in the movie which later the data is connected with some theories. This study also aims to find out the literary meaning of the movie Parasite, specifically the representation of social class through some literary research.